2013
DOI: 10.1016/j.urology.2012.11.034
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Quantify Male Pelvic Floor Displacement From 2D Transperineal Ultrasound Images

Abstract: Objective To develop a method to quantify displacement of pelvic structures during contraction of the pelvic floor muscles from transperineal ultrasound images in men and investigate the reliability of the method between days. Methods Ten healthy male volunteers (aged 28 – 41 years) attended two separate data collection sessions. Ultrasound images were recorded during voluntary pelvic floor muscle contractions in cine-loop (video) format with the transducer aligned in the mid-sagittal plane on the perineum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 11 publications
3
56
0
Order By: Relevance
“…Anatomical studies describe three striated muscle complexes that have the potential to develop urethral pressure. These muscle complexes are the puborectalis/pubovisceralis (PR) which draws the urethra ventrally and elevates the bladder, the striated urethral sphincter (SUS) which draws the urethra dorsally, and the bulbocavernosus (BC) which compresses the urethra at the bulb of penis. Although the nervous system controls these muscles independently, attention to the contribution of each muscle to continence has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical studies describe three striated muscle complexes that have the potential to develop urethral pressure. These muscle complexes are the puborectalis/pubovisceralis (PR) which draws the urethra ventrally and elevates the bladder, the striated urethral sphincter (SUS) which draws the urethra dorsally, and the bulbocavernosus (BC) which compresses the urethra at the bulb of penis. Although the nervous system controls these muscles independently, attention to the contribution of each muscle to continence has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this protocol may be useful in differentiating between therapy responders and non-responders to inform intervention planning and enhance targeting of interventions to those patients whom would most benefit. Combining this transperineal approach with other sonographic investigations of the pelvic floor, such as those evaluating structure orientation and dynamic movements (Davis et al 2011; Stafford et al 2012; Stafford et al 2013), may lead to a robust evaluation protocol for individuals with CPPS.…”
Section: Discussionmentioning
confidence: 99%
“…The first report using this approach meant to evaluate the orientation of anal-pelvic structures, i.e., anorectal angle and levator plate angle (Davis et al 2011). A similar transperineal approach has been reported in evaluation of the displacement and dynamic changes of pelvic structures during contraction of pelvic floor and anorectral muscles (Stafford et al 2012; Stafford et al 2013). These studies utilized a low-frequency curvilinear probe with data collection in a sagittal plane to evaluate the entire pelvic region.…”
Section: Introductionmentioning
confidence: 97%
“…Stafford et al measured the contraction of the pelvic floor muscles, clearly defining the displacement of the urethrovesical junction, ano--rectal junction and distal urethra in healthy young men (10,12). Davis et al measured men with chronic pelvic pain syndrome and concluded that men with pain had a smaller ano-rectal angle compared to men without pain (11).…”
Section: Discussionmentioning
confidence: 99%